Nutrient uptake dynamics of Gloriosa for cut flower - Ricardo Daniel Haussecker; Doris Irene Bischoff; Diego Alejandro Mata; Rodrigo Guzman Veron; Daniel Enrique Morisigue (Ornamental Horticulture, 2023)
Gloriosa superba L. is a recently introduced tropical species in Argentina, cultivated as a cut flower. It is extremely important to know the nutritional demands of the crop to provide the optimal amounts of nutrients at each stage, achieving quality and good yield in flowers, reducing production costs and environmental impact. The objective of this work was to determine the dynamics of nutrient absorption in the cultivation of G. superba for cut flowers, to facilitate the creation of a fertilization program, in order to avoid crop deficiencies and contribute to sustainable production. Tuber composition analyzes were carried out and, on the other hand, an essay was installed in greenhouse beds, taking samples at seven moments of the cycle. Fresh matter and dry matter of stems, leaves, flowers, tubers, roots and chemical analysis of aerial organs were measured to obtain the absorption curve. It was verified that only around 20% of each nutrient is provided by the tuber, being necessary the external contribution from initial stages of the crop. The rate of growth and accumulation of dry matter was shown as a double sigmoid, with maximum peaks      in the vegetative stage of stem elongation and beginning of flowering. Nutrient amounts were absorbed in the following order: N>K>Mg>Ca>P>Fe>Mn>Zn>Cu. Fertilization rich in N, P, and Fe is recommended in the vegetative stage, balanced during the visible shoot stage, and rich in Ca, K, Mg, Mn, Zn, and Cu during flowering.